Topical gel formulation and stability assessment of platelet lysate based on turbidimetric method - Soliman Mohammadi Samani; Akram Jamshidzade; Seyed Modjtaba Seyed Raoufi; Zeinab Mardani (Shiraz University of Medical Sciences, 2015)
Platelet-rich growth factors have attracted attentions of scientists and clinical practitioners who are involved in wound healing and regenerative medicine extensively, according to their unprecedented potential of promoting and catalyzing healing process. Platelet-rich growth factors are cost-benefit, available and more stable than recombinant human growth factors. These appealing characteristics have converted PRGF to one of the popular candidates for treatment of variety of wounds. According to these valuable properties, we decided to formulate and assess the effect of different excipients on the stability of such valuable protein based formulations. Different excipients have been chosen according to their effective ness on the stability of proteins and their application in other similar formulations. The stabilizing effect of excipients was evaluated by measuring heat-induced aggregation of growth factors by turbidimetric assay. Glycerol, glycine and dextrose were chosen as stabilizing excipients for these formulations. The results show that dextrose has more stabilizing effect on prevention of heat induced aggregation of the platelet lysate growth factors than glycerol and glycine. All of the formulations also contained antioxidant, chelating agents, preservative and carbopol934 in order to form appropriate gel.